Effect of microstructure, deformation mode and rate on mechanical behaviour of electron-beam melted Ti-6Al-4V and Ti-1.5Al-6.8Mo-4.5Fe alloys - Ivasishin, O.M.; Akhonin, S.V.; Savvakin, D.G.; Berezos, V.A.; Bondarchuk, V.I.; Stasyuk, O.O.; Markovsky, P.E. (Успехи физики металлов, 2018)
Two commercial costefficient titanium alloys—a lowalloyed α+βti–6Al–4V (mas.%) and a metastable βalloy ti–1.5Al–6.8Mo–4.5Fe melted with a single electronbeam cold hearth melting approach—are employed in a present study as program materials. the influence of microstructure formed by means of the subsequent thermomechanical and heat treatments on both the mechanical behaviour (evaluated by the deformation energy, UD) when tested using standard methods with different deformation rates and the ballistic resistance of plate materials is investigated. На прикладі двох промислових економно леґованих титанових стопів, — малолеґованого α + β-стопу ti–6Al–4V (мас.%) і метастабільного βстопу ti–1,5Al–6,8Mo–4,5Fe, — виготовлених одноразовим електроннопроменевим топленням з проміжною ємністю, вивчено вплив формованої за подальших (термомеханічного та термічного) оброблянь мікроструктури на механічну поведінку (виражену через енергію деформації UD) при випробуваннях з різними швидкостями деформації та балістичну стійкість. На примере двух промышленных экономно легированных титановых сплавов, — малолегированного α + βсплава Тi–6Al–4V (масс.%) и метастабильного βсплава ti–1,5Al–6,8Mo–4,5Fe, — приготовленных однократной электроннолучевой плавкой с промежуточной ёмкостью, изучено влияние формируемой при последующих (термомеханической и термической) обработках микроструктуры на механическое поведение (выраженное через энергию деформации UD) при ис пы таниях с разными скоростями деформации и баллистическую стойкость.